(untitled) (Mongolian Journal of Humanities and Social Sciences, 2024)
An important topic of content research is studying ‘the value’ of the dear guest in a portrait interview. Famous people have their own values. Therefore, it is important to clarify the skills and content of the program, studying the values of the ‘Mongolian gentleman’ who is the subject of the portrait interview program. In this article, we set the task of studying the values of the interviewer in the interview program ‘Gentleman’, recently released in Mongolia and Inner Mongolia, using a special technique and comparing it. The study found that ‘gentlemen’ have common and unique values that indicate the character of the owner. An important topic of content research is studying ‘the value’ of the dear guest in a portrait interview. Famous people have their own values. Therefore, it is important to clarify the skills and content of the program, studying the values of the ‘Mongolian gentleman’ who is the subject of the portrait interview program. In this article, we set the task of studying the values of the interviewer in the interview program ‘Gentleman’, recently released in Mongolia and Inner Mongolia, using a special technique and comparing it. The study found that ‘gentlemen’ have common and unique values that indicate the character of the owner. Хөрөг ярилцлагын “эрхэм зочны” үнэт зүйлсийг судалсан нь Хураангуй: Хөрөг ярилцлагын нэвтрүүлгийн эрхэм зочин, хүмүүний “үнэт зүйлс”-ийг судлах нь агуулгын судалгааны нэг чухал сэдэв мөн. Олны танил болсон эрхэм хүмүүс өөрийн гэсэн үнэт зүйлтэй байдаг. Иймд хөрөг ярилцлагын нэвтрүүлгийн объект болох “монгол эрхэм хүмүүн”-ий эрхэмлэх үнэт зүйлсийг судалснаар нэвтрүүлгийн ур чадвар, агуулгын цөм зүйлийг тодруулах ач холбогдолтой. Энэхүү өгүүлэлдээ Монголд болон Өвөр монголд сүүлийн үед гарч байгаа “эрхэм хүмүүн”-ий хөрөг ярилцлагын нэвтрүүлгийн ярилцагчийн үнэт зүйлийг тусгайлсан арга зүйгээр, мөн харьцуулан судлахыг зорив. Судалгааны үр дүнд “эрхэм хүмүүс”-т нийтлэг болон өвөрмөц үнэт зүйл бүрэлдэж, тухайн эзнийхээ мөн чанарыг илтгэж буй нь харагдлаа. Түлхүүр үг: хөрөг ярилцлага, зочин ярилцлагч, эрхэм хүмүүн, үнэт зүйл, үнэт зүйлийн давтамж